2020
DOI: 10.3390/ijms21249665
|View full text |Cite
|
Sign up to set email alerts
|

Linking ABCC6 Deficiency in Primary Human Dermal Fibroblasts of PXE Patients to p21-Mediated Premature Cellular Senescence and the Development of a Proinflammatory Secretory Phenotype

Abstract: Pseudoxanthoma elasticum (PXE) is a rare autosomal-recessive disorder that is mainly caused by mutations in the ATP-binding cassette sub-family C member 6 (ABCC6) gene. Clinically PXE is characterized by a loss of skin elasticity, arteriosclerosis or visual impairments. It also shares some molecular characteristics with known premature aging syndromes like the Hutchinson–Gilford progeria syndrome (HGPS). However, little is known about accelerated aging processes, especially on a cellular level for PXE now. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…The senescent cells exhibit increased cell-cycle inhibitors p21 and p16 and increased β-galactosidase activity, loss of nuclear high mobility group box 1 (HMGB1), and decreased lamin B1 [ 8 , 64 ]. These senescent cells produce senescence-associated secretory phenotypes (SASPs) such as pro-inflammatory cytokines and immune modulators [ 65 ]. Because these senescent cells have harmful effects on surrounding cells, recent strategies have aimed at the selective killing of senescent cells (called senolytic) or inhibiting SASPs without affecting the neighbor cells [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The senescent cells exhibit increased cell-cycle inhibitors p21 and p16 and increased β-galactosidase activity, loss of nuclear high mobility group box 1 (HMGB1), and decreased lamin B1 [ 8 , 64 ]. These senescent cells produce senescence-associated secretory phenotypes (SASPs) such as pro-inflammatory cytokines and immune modulators [ 65 ]. Because these senescent cells have harmful effects on surrounding cells, recent strategies have aimed at the selective killing of senescent cells (called senolytic) or inhibiting SASPs without affecting the neighbor cells [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding a possible pathophysiological link between T50 and PXE disease severity, in vitro studies have shown that exposing vascular smooth muscle cells to secondary CPPs provokes a substantial inflammatory and procalcifying reaction, and increases oxidative stress [48,49]. As oxidative stress and increased cytokine production-as part of an overlapping process of excessive DNA damage response and premature senescence-have recently been shown to be involved in PXE pathogenesis, the dose-dependent damaging effects of secondary CPPs (as reflected by T50) might directly link T50 to the molecular process of PXE-related ectopic calcification [32,50].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, our group and others have recently demonstrated the involvement of excessive DNA damage response (DDR) signaling, mediated via the PARP1-STAT-IL6-RUNX2 axis, in PXE pathogenesis [ 39 , 40 ]. Indeed, overaction of DDR pathways including ATM, p21, and p53 results in premature senescence in PXE fibroblasts and contributes to the EC process [ 39 , 41 ]. On the contrary, PARP1 inhibition by means of minocycline, which is also a known ROS scavenging molecule, significantly reduced EC in both PXE fibroblasts, zebrafish, and mice models [ 39 , 42 ].…”
Section: Mitochondrial Dysfunction and Oxidative Stress In Pseudoxant...mentioning
confidence: 99%